The Impact of Agrotourism 'Waaida Farm' on Community Empowerment, Pamulihan District, Sumedang Regency - Dasipah, Euis; Erviany, Nita; Gantini, Tuti (Journal of Indonesian Tourism, Hospitality and Recreation, 2021)
ABSTRACTThis study aims to determine how Waaida Farm manages agro-tourism and to measure the impact of agro-tourism from the empowerment of the surrounding farmer's community. The Farm is located in Sumedang Regency and has natural potentials in agriculture and tourism which offers a unique experience. The concept of agro-tourism offers a medium for education, culture, promotion of local products, social, economic growth and community empowerment. With the existence of the Farm, the characteristics of the community have changed positively. The research method used is the case study and primary data were obtained from 30 farmers who work at agro-tourism. From the results of the paired t-student difference test ( Paired Sample T Test ) it can be concluded  that Agro-tourism has a positive impact on the empowerment of the surrounding community not only from increasing participation, but also independence and accessibility for farmers community.Keywords: Agro-tourism, Community Empowerment